Strategi Pemanfaatan Crowdfunding dalam Mendukung Pembiayaan Pendidikan di Era Digital - Madhar Amin (Business Finance Analyst Co., 2024)
Crowdfunding has become an innovative solution to overcome funding challenges in the education sector. This study explores the role of crowdfunding platforms in supporting education financing through the donation-based crowdfunding model. Using a qualitative approach based on literature studies, this study identifies the advantages, challenges, and relevant strategies in implementing education crowdfunding. The results of the analysis show that crowdfunding offers ease of access, cost efficiency, and transparency that can increase donor trust. In the context of education, this approach can support various needs such as the provision of scholarships, the construction of school facilities, and teacher training. However, the success of the campaign relies heavily on effective digital marketing strategies, such as the use of social media, video storytelling, and community engagement. The main challenges include competition between campaigns, low digital literacy, and limited internet access in some regions. Therefore, multi-stakeholder collaboration involving governments, educational institutions, technology companies, and local communities is needed to improve the effectiveness of campaigns. With the adoption of supportive regulations, transparency, and strong accountability, crowdfunding can be a sustainable solution to strengthen access and quality of education, while building a culture of mutual cooperation in the digital era.